Presidential Position-Taking, Presidential Success, and Interest Group Activity. Issue 1 (2nd January 2019) - McKay, Amy Melissa; Webb, Brian
Abstract: Do lobby groups help the American president achieve policy objectives? Existing research seldom evaluates interest groups and the president in conjunction, and as a result we have little systematic knowledge about how groups respond to presidential actions or whether they assist in realizing the president's policy agenda. Building on existing data obtained through interviews with 776 lobbyists, combined with variables we generate describing issue salience, congressional attention, the political context, and policy adoption, we show that interest groups adjusted their lobbying activity to better reflect the president's voiced preferences. Despite this strategy, we find that lobby groups had no significant marginal effect on policy adoption when controlling for the overwhelming influence of the president. The strong association between policy adoption and position-taking by the president withstands the inclusion of five alternative variables found in previous studies to condition the influence of the president over policy adoption.